NOTES TO THE RESEARCH METHODS OF THE INFORMATION SYSTEM FOR ORGANIZATION MANAGEMENT: NOTES TO THE RESEARCH METHODS OF THE INFORMATION SYSTEM FOR ORGANIZATION MANAGEMENT - Dyankov, Plamen; Stoyanov, Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The choice of research methods essentially depends on the basic concept which corresponds to the nature and structure of the researched object and it suggests identity of the choice with their nature and composition.